Demystifying biosimilars: development, regulation and clinical use. (30th November 2018) - Rugo, Hope S; Rifkin, Robert M; Declerck, Paul; Bair, Angel H; Morgan, Geraint
Biologics are an integral component in the treatment of various diseases. However, limited patient access to these medicines remains a significant global challenge, prompting development of safe and effective biosimilars. A biosimilar is 'highly similar to a reference (originator) product, for which there are no clinically meaningful differences between the two products in terms of safety, purity and potency'. Biosimilars have the potential to offer possible benefits, including lower treatment costs, thereby increasing patient access and clinical use, which may lead to better overall outcomes. Improved understanding of biosimilars may enhance confidence and trust in these agents. As increasing numbers of biosimilars achieve regulatory approval, this overview aims to address enduring knowledge gaps regarding the development and use of biosimilars.